Some indicators for assessing the stock of redtail scad (Decapterus kurroides Bleeker, 1855) in Palabuhanratu Waters, West Java, Indonesia - Chodrijah Umi; Tirtadanu; Prihatiningsih; Fauzi Muh.; Wagiyo Karsono; Restiangsih Yoke Hany (E3S Web of Conferences, 2023)
The redtail scad fish (Decapterus kurroides, Bleeker 1855) is a dominant small pelagic fish that has high economic value. Therefore, it is important to maintain and manage redtail scad resources in an efficient and sustainable approach. This study was carried out in the Palabuhanratu Fishing Port, West Java in 2019. The objective of this study was to assess the stock of redtail scad as a basis for their sustainable management. The findings revealed that the distribution of the 3076 samples' total length ranged from 14.7 to 45.0 cm, with an average of 25.69 cm. The growth pattern was positively allometric. The sex ratio between males and females is unbalanced, and the most significant proportion of mature females was found in July. The bottom longline and gillnet catch a larger size of redtail scad than the handline. A legal size of 26 cm was recommended for the optimal size of the redtail scad. The asymptotic length (L∞) and growth rate (K) were 45.43 cm and 0.61 year-1, respectively. The exploitation rate (E) was 0.52 year-1, indicating that a fisheries status leads to an overfishing condition.